If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = -93 + -8x Reorder the terms: 5 + 6x = -93 + -8x Solving 5 + 6x = -93 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 5 + 6x + 8x = -93 + -8x + 8x Combine like terms: 6x + 8x = 14x 5 + 14x = -93 + -8x + 8x Combine like terms: -8x + 8x = 0 5 + 14x = -93 + 0 5 + 14x = -93 Add '-5' to each side of the equation. 5 + -5 + 14x = -93 + -5 Combine like terms: 5 + -5 = 0 0 + 14x = -93 + -5 14x = -93 + -5 Combine like terms: -93 + -5 = -98 14x = -98 Divide each side by '14'. x = -7 Simplifying x = -7
| -14-4x=10-10x | | 3+11x=73+x | | 6x-3=13x-73 | | 2.38x+6.8=3.94x+-3.44 | | 7a=14 | | -104-9x=9x+22 | | -y+4y=48 | | 2x+10=-100-9x | | 48=-y+4y | | 3x+10=50 | | 128-5x=5x+8 | | 6w+19w=100 | | 2x+14=28 | | 2x-1=9x-71 | | 5x+33=15x-87 | | y-1=12 | | x^5+x=96 | | 5x+x=96 | | 6a=54 | | p+8-8=-6 | | -8n-7=-12 | | 4xy+8=36 | | 7x+4x-8x-5=13 | | 11x-16=6x+4 | | 4-2x=-12 | | 7+5x=57 | | w-19=-100 | | -2*x=-100 | | y=3x(y-1) | | x+16=-100 | | 5x+10=15x | | x*100=100 |